Komitmen Profesionalisme Guru Bersertifikasi dalam Pembelajaran (Studi Kasus Pada Guru Madrasah Kota Jambi) - Jailani, M. Syahran (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2016)
The purpose of this research is to reveal the commitment of the professional teachers (civil servant) who teach in a private madrassa in Jambi to enhance the performance of instructional process. The research informants include civil servant teachers teaching in several private madrassa in Jambi. This qualitative research employs phenomenologist approach, referring to eleven steps by Spradley (1980). The research exemplifies that the professionalism of civil servant teachers at Jambi needs advancing. Although the teachers recognize some obstacles, they realize the commitment and responsibility as the professional teacher is essential to improve the instruction and self-quality. Secondly, it is found that the governments at Jambi do less-optimum efforts to elevate the professionalism of certificated-teachers. Then, the supervisions through education and training (Diklat) have not been well-socialized and the activities of pursuing Master degree program remain incidental. The agenda of teacher network (MGMP), Teacher Working Group (KKG) and School Principal Working Groups (KKKS) are not routinely conducted. Besides, the coordination obstacle among stakeholders is a major problem for the professionalism. The classical problem about funding also comes from the stakeholders in determining policy. Consequently, the policy about certified teachers and their development to support the educational process must be properly established.